2012
DOI: 10.4049/jimmunol.1102349
|View full text |Cite
|
Sign up to set email alerts
|

Shifting of Immune Responsiveness to House Dust Mite by Influenza A Infection: Genomic Insights

Abstract: Respiratory viral infections have been associated with an increased incidence of allergic asthma. However, the mechanisms by which respiratory infections facilitate allergic airway disease are incompletely understood. We previously showed that exposure to a low dose of house dust mite (HDM) resulted in enhanced HDM-mediated allergic airway inflammation, and, importantly, marked airway hyperreactivity only when allergen exposure occurred during an acute influenza A infection. In this study, we evaluated the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
1
9
0
3
Order By: Relevance
“…Support for this finding can be found in recent studies reporting that children at the highest risk of developing asthma are those who, before 2 years of age, suffered from viral respiratory infections and allergic sensitization . It has also been postulated, based on results from a mouse model, that viral respiratory infections prime immunological pathways and lead to an increased responsiveness to house dust mite allergens, subsequent allergic sensitization and asthma . On the other hand, there is evidence for a causal relationship between allergic sensitization and an increased susceptibility to viral infections leading to asthma .…”
Section: Discussionsupporting
confidence: 88%
“…Support for this finding can be found in recent studies reporting that children at the highest risk of developing asthma are those who, before 2 years of age, suffered from viral respiratory infections and allergic sensitization . It has also been postulated, based on results from a mouse model, that viral respiratory infections prime immunological pathways and lead to an increased responsiveness to house dust mite allergens, subsequent allergic sensitization and asthma . On the other hand, there is evidence for a causal relationship between allergic sensitization and an increased susceptibility to viral infections leading to asthma .…”
Section: Discussionsupporting
confidence: 88%
“…54 Two related pathways have been described that might account for these observations. First, as initially reported in mouse models, [55][56][57] influenza and parainfluenza infections lead to upregulation of expression of the myeloid version of the high-affinity IgE receptor (FcεRI) on lung DCs; the precise mechanism or mechanisms involved remain to be elucidated but can include signals from a subset of incoming neutrophils recruited to the infection site. 56 It was suggested that cross-linking of this receptor with IgE directed against viral antigens might trigger local T H 2 cytokine production by virus-specific T H 2 memory cells, 57 but the existence of the latter remains unproved.…”
Section: Role Of Viral Respiratory Tract Infection In Asthma Cause Anmentioning
confidence: 97%
“…Alternatively, it has been shown that upregulation of this receptor in the parainfluenza model in animals presensitized to house dust mite allergen was associated with development of hyperresponsiveness to local allergen challenge, resulting in enhanced local production of T H 2 cytokines and reduced lung function. 55 The operation of a comparable pathway in human subjects is suggested by airway biopsy data demonstrating the presence of FcεRI 1 DCs in the bronchial mucosa of asthmatic patients 58 and in particular that this expression increases during periods of active disease. 59 Recent studies on acute severe asthma exacerbations in children resulting in hospitalization have shed some light on the underlying pathways involved.…”
Section: Role Of Viral Respiratory Tract Infection In Asthma Cause Anmentioning
confidence: 99%
“…It was shown that murine parainfluenza LRTI causes an up-regulation of the high-affinity IgE receptor on lung antigen presenting cells, production of Th2 inflammatory cell and inflammatory mediators, and eventually results with an increased immune response to inhalant allergens 2024 . The importance of the viral infection as the initial event (“the first hit”) to create airway allergic inflammation was further demonstrated in additional models involving innate immunity and invariant natural killer T cells 25, 26 .…”
Section: Viral Bronchiolitis In Early Infancy and Future Asthma: “Thementioning
confidence: 99%